Determination of Cut-Off Index of Reactive HBsAg Based on Confirmatory Test at Dr. Moewardi Hospital - Ellya Latifah Ilyas; JB. Suparyatmo; Amiroh Kurniati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
HBsAg confirmatory test is required to confirm false reactive HBsAg due to non-specific binding of antigen withantibody. HBsAg confirmatory test cannot be performed in every laboratory due to the high price of reagents, short reagentshelf life, prolonged turnaround time, and increasing complexity of the test. This study aimed to determine the HBsAg COI(cut-off unit) cut-off point, which requires a confirmatory HBsAg test on the COBAS e411 analyzer with the ECLIA method.An observational analytic study with a cross-sectional approach was performed on 59 patients who underwent the HBsAgtest at Dr. Moewardi Hospital, Surakarta in September-October 2020 on the Cobas e411 analyzer with the ECLIA method.The best analytical performance of cut-off index of reactive HBsAg was determined using the ROC curve and AUC. Theresults of initial HBsAg COI showed the following results: borderline with a mean: 0.975±0.0014 and reactive with a medianof 4.38 (1.03-10)). The confirmatory test showed 59.8% reactive, 22.2% non-reactive, 13.8% not valid and 4.2%indeterminate results. The cut-off value for reactive HBsAg was 4.34 with an AUC of 0.818 (95% CI: 0.713 - 0.923; p=0.054), asensitivity of 72.1% and a specificity of 87.5%. The initial cut-off of HBsAg index at 4.34 COI showed the best analyticalperformance with a sensitivity of 72.1% and specificity of 87.3%. Therefore, it can be used to determine HBsAg results thatrequire HBsAg confirmatory examination on the Cobas e411 analyzer with the ECLIA method.